Emerging disciplinary voices - Stock, Ingrid; Karsten, Andrea; Eik-Nes, Nancy Lea (Sakprosa)
While referencing is an important feature of academic writing, many students struggle with using sources. This struggle seems to be due, in part, to the tension students experience when advised to cite sources (i.e., others’ voices) on the one hand, and to demonstrate their own disciplinary voice on the other hand. The aim of this article is to contribute to the understanding of source use, presenting a figure that illustrates gradients of students’ engagement with sources in various sections of their bachelor’s theses. Based on Bakhtin’s idea that a writer’s voice gradually emerges out of others’ words, and the terms knowledge telling and knowledge transforming, we developed a continuum that might help to understand the complexity of source use. We arrived at this continuum through the qualitative exploration of students’ use of sources in 15 bachelor’s theses from the humanities in one Norwegian university. In this article, we illustrate the continuum through extracts from the students’ theses, showing how issues of voice are intertwined with students’ engagement with sources. We propose that understanding the various functions of sources as they are typically used in the disciplines will help students to develop and demonstrate their disciplinary voices. Moreover, the continuum provides a foundation for fruitful discussions of writing practices that raise critical awareness about implicit expectations concerning source use and issues of voice in academic writing.
Keywords: Automotive Engineering

Assessing the Impact of the Powder Production Method on Ceramic-filled Polyamide Composites made by Laser Sintering - Kletetzka, Ivo; Neitzel, Fabian; Schmid, Hans-Joachim (Proceedings of the 34th Annual International Solid Freeform Fabrication Symposium)
Polymer composites represent the industry standard in injection molding for the production of plastic components with increased requirements in terms of heat resistance and stiffness. In the field of laser sintering (LS), these materials are less common so far. In order to extend the available material variety for the LS process, new ceramic-filled Polyamide 613 powders are investigated within the scope of this work. Here, the resulting properties from two different powder production methods are compared. One filled powder is produced by dry blending and the other powder with the same filler and filling ratio is produced by encapsulating the filler particles inside the polymer particles within the dissolution-precipitation process. It was found that encapsulating the filler particles can provide certain benefits for the processability, for example an improved powder flowability or better filler dispersion. However, encapsulating the filler also alters the thermal properties of the precipitated powder.
Keywords: Additive Manufacturing; Laser Sintering; Filled Materials; Composites; Polyamide 613

Halogen-Free Flame Retardant Powder Materials for Laser Sintering: Evaluation and Process Stability Analysis - Neitzel, Fabian; Kletetzka, Ivo; Schmid, Hans-Joachim (Proceedings of the 34th Annual International Solid Freeform Fabrication Symposium)
The high flammability of components manufactured by laser sintering (LS) using standard polyamide 12 (PA12) powder still severely restricts their use in industries such as electronics, aviation, and transportation. A key factor for the further establishment of LS is the expansion of the material portfolio with, for example, refreshable and halogen-free flame-retardant (FR) powder materials. Accordingly, various halogen-free FRs are investigated in this work and evaluated with respect to their use in LS. First, their decomposition behavior and mode of action are examined. Subsequently, the additives are dry blended with PA12 to investigate properties relevant for LS, such as particle morphology, thermal behavior and melt viscosity. Afterwards, test specimens for UL94 vertical flame-retardancy tests are produced by processing the dry blends on an EOS P3 LS system. Finally, the process stability of the process-aged powder blends is investigated by again examining the thermal behavior and melt viscosity.
Keywords: Additive Manufacturing; Laser Sintering; Flame Retardant; Polyamide 12

Coworking - Krause, Ina (Arbeit)
Zusammenfassung Der Beitrag beschäftigt sich mit dem Konzept Coworking und arbeitet auf Basis eigener empirischer Daten heraus, wie dieses Konzept im Zuge seiner wachsenden Verbreitung und der Etablierung von Coworking-Spaces als ‚dritten Orten der Arbeit‘ Legitimität für neue Gestaltungsideen und Wertvorstellungen von Büroarbeit generiert. Coworking-Spaces werden dabei als ‚dritte Orte‘ definiert, die dem Raumkonzept der Schaffung einer flexibel anpassbaren und Kreativität fördernden Arbeitsumgebung für Büroarbeiter:innen folgen. Das Geschäftskonzept Coworking-Space wird inzwischen aber auch als alternatives Organisationsmodell von Arbeit wahrgenommen. Dem Beitrag liegt das Forschungsinteresse zugrunde zu erkunden, wie und in welchen Variationen das Konzept Coworking in Büroarbeitsorganisationen, die sich selbst als Coworking-Space bezeichnen, adaptiert und praktisch umgesetzt wird. Nachgezeichnet wird, inwiefern Coworking als alternatives Gestaltungsmodell oder, im Sinne von Meyer und Rowan, Rationalisierungskonzept der Organisation von Arbeit Elemente eines neuen Normalitätsverständnisses von Büroarbeit generiert, welches über Betreiber:innen von Coworking-Spaces und Coworker:innen inzwischen in die Breite der Arbeitsgesellschaft getragen wird.
Keywords: Industrial and Manufacturing Engineering

Im Osten nichts Neues? Über (un)bekannte Akteure in der regionalen Weiterbildungslandschaft. - Krause, Ina; Biess, Anne; Bohlinger, Sandra (bwp@ Berufs- und Wirtschaftspädagogik – online)

Entkoppelte Arbeitswelten - Krause, Ina
Die Strukturen der industriell geprägten Arbeitsgesellschaft werden durch den zunehmenden Einsatz automatisierter und digitaler Technologien sowie den Ausbau der Infrastruktur des Internets maßgeblich verändert. Gleichzeitig lässt sich eine intensive Flexibilisierung vertrauter Strukturen betriebszentrierter Organisationsformen von Beschäftigung beobachten. Ina Krause beschreibt einzelne Dynamiken auf der gesellschaftlichen Mesoebene und trägt damit zur Debatte über die nachhaltige Gestaltung der digitalen und virtuellen Arbeitsgesellschaft in Deutschland bei.

Frontmatter - Krause, Ina; Jacobsen, Heike; Gerhards, Christian (Arbeit)
Keywords: Industrial and Manufacturing Engineering

Business Reputation Systems based on Blockchain Technology—A Risky Advance - Hemmrich, Simon (Proceedings of 31st European Conference on Information Systems (ECIS 2023))
Reputation is indispensable for online business since it supports customers in their buying decisions and allows sellers to justify premium prices. While IS research has investigated reputation systems mainly as review systems on online platforms for business-to-consumer (B2C) transactions, no proper solutions have been developed for business-to-business (B2B) transactions yet. We use blockchain technology to propose a new class of reputation systems that apply ratings as voluntary bonus payments: Before a transaction is performed, customers commit to pay a bonus that is granted if a service provider has performed a service properly. As opposed to rival reputation systems that build on cumulated ratings or reviews, our system enables monetized reputation mechanisms that are inextricably linked with online transactions. We expect this system class to provide more trustworthy ratings, which might reduce agency costs and serve quality providers to establish a reputation towards new customers, building on second-order trust.
Keywords: Trust; Risk; Reputation System; Blockchain Technology; Business Reputation System.

Nonlinear Dielectric Geometric-Phase Metasurface with Simultaneous Structure and Lattice Symmetry Design - Liu, Bingyi; Geromel, René; Su, Zhaoxian; Guo, Kai; Wang, Yongtian; Guo, Zhongyi; Huang, Lingling; Zentgraf, Thomas (ACS Photonics)
In this work, we utilize thin dielectric meta-atoms placed on a silver substrate to efficiently enhance and manipulate the third-harmonic generation. We theoretically and experimentally reveal that when the structural symmetry of the meta-atom is incompatible with the lattice symmetry of an array, some generalized nonlinear geometric phases appear, which offers new possibilities for harmonic generation control beyond the accessible symmetries governed by the selection rule. The underlying mechanism is attributed to the modified rotation of the effective principal axis of a dense meta-atom array, where the strong coupling among the units gives rise to a generalized linear geometric phase modulation of the pump light. Therefore, nonlinear geometric phases carried by third-harmonic emissions are the natural result of the wave-mixing process among the modes excited at the fundamental frequency. This mechanism further points out a new strategy to predict the nonlinear geometric phases delivered by the nanostructures according to their linear responses. Our design is simple and efficient and offers alternatives for the nonlinear meta-devices that are capable of flexible photon generation and manipulation.
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics; Biotechnology; Electronic; Optical and Magnetic Materials

The role of digital technologies in transforming student learning landscapes - Rezat, Sebastian; Geiger, Vince (Handbook of Digital Resources in Mathematics Education)

Implementing profession orientation as a design principle for overcoming Klein’s second discontinuity – preservice teacher’s perspectives on interface activities in the context of a geometry course - Hoffmann, Max; Biehler, Rolf (ZDM – Mathematics Education)
Intending to counteract Klein’s second discontinuity in teacher education, we explored and applied the innovation of “interface ePortfolio” in the context of a geometry course for preservice teachers (PSTs). The tool offers the possibility of implementing the design principle of profession orientation. In the article, we theoretically clarify what we understand by this principle and locate our innovative concept against this theoretical background. We empirically investigate the extent to which counteraction against the second discontinuity is successful by analyzing reflection texts created in the interface ePortfolio, focusing on PSTs’ perspectives. Our qualitative content analysis shows that most of them perceive the innovation as helpful in the intended sense and indicates that the course concept, in general, and the interface ePortfolio, in particular, have helped establish relevant links between the course content and their later work as teachers.
Keywords: General Mathematics; Education

Towards comparable ratings: Exploring bias in German physician reviews - Kersting, Joschka; Maoro, Falk; Geierhos, Michaela (Data & Knowledge Engineering)
In this study, we evaluate the impact of gender-biased data from German-language physician reviews on the fairness of fine-tuned language models. For two different downstream tasks, we use data reported to be gender biased and aggregate it with annotations. First, we propose a new approach to aspect-based sentiment analysis that allows identifying, extracting, and classifying implicit and explicit aspect phrases and their polarity within a single model. The second task we present is grade prediction, where we predict the overall grade of a review on the basis of the review text. For both tasks, we train numerous transformer models and evaluate their performance. The aggregation of sensitive attributes, such as a physician’s gender and migration background, with individual text reviews allows us to measure the performance of the models with respect to these sensitive groups. These group-wise performance measures act as extrinsic bias measures for our downstream tasks. In addition, we translate several gender-specific templates of the intrinsic bias metrics into the German language and evaluate our fine-tuned models. Based on this set of tasks, fine-tuned models, and intrinsic and extrinsic bias measures, we perform correlation analyses between intrinsic and extrinsic bias measures. In terms of sensitive groups and effect sizes, our bias measure results show different directions. Furthermore, correlations between measures of intrinsic and extrinsic bias can be observed in different directions. This leads us to conclude that gender-biased data does not inherently lead to biased models. Other variables, such as template dependency for intrinsic measures and label distribution in the data, must be taken into account as they strongly influence the metric results. Therefore, we suggest that metrics and templates should be chosen according to the given task and the biases to be assessed.
Keywords: Language model fairness; Aspect phrase classification; Grade prediction; Physician reviews

Verifying Software and Reconfigurable Hardware Services - Wehrheim, Heike; Platzner, Marco; Bodden, Eric; Schubert, Philipp; Pauck, Felix; Jakobs, Marie-Christine (On-The-Fly Computing -- Individualized IT-services in dynamic markets)

Compute Centers I: Heterogeneous Execution Environments - Hansmeier, Tim; Kenter, Tobias; Meyer, Marius; Riebler, Heinrich; Platzner, Marco; Plessl, Christian (On-The-Fly Computing -- Individualized IT-services in dynamic markets)

Flexible Industrial Analytics on Reconfigurable Systems-On-Chip - Boschmann, Alexander; Clausing, Lennart; Jentzsch, Felix; Ghasemzadeh Mohammadi, Hassan; Platzner, Marco (On-The-Fly Computing -- Individualized IT-services in dynamic markets)

Tiere in der Theologie? Zur Überwindung der Tiervergessenheit. Der Blog des Zentrums für Komparative Theologie und Kulturwissenschaften - Herdramm, Henrike (BloKK. Der Blog des Zentrums für Komparative Theologie und Kulturwissenschaften)

Gegen das Verstummen. Texthermeneutische Reflexionen zu Ironie in der Textsortenwelt des Gettos Litzmannstadt - Markewitz, Friedrich
Unmittelbar nach der nationalsozialistischen Machtergreifung setzte eine umfassende gesellschaftliche, juristische und existentielle Ausgrenzung jüdischer Akteure ein. Dem Zerbrechen bisheriger Welt- und Normverständnisse zu begegnen wurde zu einer existentiellen Herausforderung sowie zu einem notwendigen Bedürfnis. Eine wichtige Strategie war der Einsatz von Humor und Ironie; auch für die Menschen des Gettos Litzmannstadt. Aus texthermeneutischer, kulturlinguistischer und sprachphilosophischer Perspektive erfasst Friedrich Markewitz – unter Berücksichtigung des Gettos als Diskursraum und dessen Textsortenwelt – Verwendungsweisen und -funktionen von Ironie und perspektiviert sie, um so einen Beitrag zur linguistischen Aufarbeitung der Kommunikation jüdischer Akteure während der Shoa zu leisten.

Kommunikative Praktiken im Nationalsozialismus
Die nationalsozialistische Gesellschaft war geprägt von vielgestaltigen kommunikativen Praktiken des sozialen und auch gewaltvollen Ein- und Ausschlusses. Gleichzeitig bildeten sich durch Widerstandshandlungen vielfältige Gegendiskurse heraus. Der Sammelband nimmt konkrete Beispiele kommunikativer Praktiken während des Nationalsozialismus in den Blick und fragt speziell danach, inwiefern diese themen-, textsorten- und akteursspezifisch gebunden waren

„Die Juden 'leben' bei ihrer betont rechnerischen Begabung am längsten schon nach dem Rasseprinzip, weshalb sie sich auch am heftigsten gegen die uneingeschränkte Anwendung zur Wehr setzen“ - Pragmalinguistische Perspektiven auf kommunikative Ausgrenzungs- und Invektivitätspraktiken in der veröffentlichen wie unveröffentlichten textgebundenen Kommunikation Martin Heideggers - Markewitz, Friedrich (Kommunikative Praktiken im Nationalsozialismus)
Invektivitäts-, Aggressions- und Gewaltpraktiken sind als sozial-kommunikative zugleich universelle Phänomene. Als kommunikative Praktiken bestimmt, können sie direkte An- griffe, z. B. in Form rassistischer und sexistischer Kommentare, aber auch indirektere Formen und Muster der Ab- wie Ausgrenzung umfassen. Ziel des Beitrags ist die Erfassung, Einordnung und Kategorisierung kommunikativer Invektivitätshandlungen in den tex- tuellen Kommunikaten Martin Heideggers. Die Linguistik kann in diesem Kontext pro- duktiv dazu beitragen, die Umfassenheit, Ausdifferenziertheit und strukturelle Relevanz der Invektivitäts- wie Gewaltsprachhandlungen als kommunikative Praktiken dieses Phi- losophen aufzuarbeiten und würde dahingehend auf bestehende Forschungsdesiderata reagieren, da sich trotz der Affinität Heideggers zu Fragen des Sprachlichen bisher kaum sprachwissenschaftliche Analysen finden, die Heidegger(s Schriften) zum Analysegegen- stand hatten. Dabei sollen nicht nur explizite Formen kommunikativen Invektivitätshan- delns erfasst werden, sondern ebenso indirektere Formen der Exklusion und Antihuma- nität, die als Teil des differenzphilosophischen Programms Heideggers als Ausgrenzungs- erfahrungen reflektiert werden können.

Zur Verwendung von wörtlicher und imaginierter (Gegen-)Rede in Tarnschriften des kommunistischen und sozialistischen Widerstands - Markewitz, Friedrich; Wilk, Nicole M. (Kommunikative Praktiken im Nationalsozialismus)
Der Beitrag bestimmt anhand der für den kommunistischen und sozialistischen Wider- stand gegen die Hitler-Diktatur charakteristischen Textgattung Tarnschrift die für den Widerstandskontext noch nicht untersuchten kommunikativen Praktiken des Gegenre- dens. Gegenreden wird in seiner dialogischen und responsiven Qualität sowohl aus text- typologischer Perspektive beschrieben als auch am Beispiel der Re-Inszenierung durch direktes und indirektes Referat interaktionslinguistisch gefasst. Schließlich werden auf- grund dieser kritischen, opponierenden und teilweise ironisierenden Bezugnahmen von Tarnschriftenartikeln auf Inhalte des NS-Diskurses und der Propaganda Tarnschriften als kommunikative Gattung der Gegenrede bestimmt. Die kommunikative Praktik des Ge- genredens wird dahingehend präzisiert, dass sie strukturell eine »Ursprungsrede« insze- niert und ein Verfahren der Gegenrede beinhaltet, mit dem sich eine widerstandsspezifi- sche Diskursposition oft auch durch das Aufdecken von Widersprüchen vollzieht. In einer Korpusanalyse von 125 Tarnschriften wird die Varianz der dialogischen Gestaltungsver- fahren des Gegenredens anhand von redeanzeigenden Verben und redebezeichnenden Nomen als Kookkurrenten von Namen wichtiger NS-Funktionäre erfasst.